Pengaruh Pembelajaran Berbasis Proyek (Aktivitas P5) terhadap Peningkatan Keterampilan Belajar Kolaboratif Siswa - Budi Lestari; Purwanto; Anggraini, Ade Eka (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Effective teaching methods are essential to facilitate students' cognitive, social, and emotional development. One of the approaches proposed in the Merdeka Curriculum is Project Based Learning (P5), which invites students to be directly involved in the learning process through real projects. The research method used is a causal quantitative method with a population of 5th grade students at SDN Karangesuki 4 with a sample size of 54 students. The data analysis technique uses a t-test with a significance level of 5%. The T-test used is a separated variant or polled variant with a calculation tool in the form of SPSS. Based on the results of the research and discussion, several conclusions can be put forward. The conclusions that will be put forward in this research are as follows. 1) There is an increase in collaboration skills between students who learn using project-based learning and students who learn using LKPD (Learner Worksheets) on the theme "Use of Used Goods" class 5 at SDN 4 Karangbesuki, Malang City. It can be seen that the post-test average for the experimental group using project-based learning was 19.058, while the post-test average for the control group was 14.117. Based on the average increase in students' collaborative learning skills, it can be concluded that the increase in students' collaborative learning skills is higher in children who use project-based learning. 2) The results of the analysis of student responses on collaborative learning skills showed that the final percentage of student responses was 81.18% which was classified as very positive. Keywords: Project Based Learning (P5); Student Learning Collaboration Skills.